L’allucinazione tra psichiatria e neuroscienze - Fargnoli, Francesco (Il sogno della farfalla, 2022)
Over the last years neuroscience has achieved considerable advancement in the understanding of brain functioning. In this article the author explores the possibility to integrate neuroscientific knowledge together with research on non-conscious mind with the aim to understand the origin of hallucinations.